SMN Depletion has a Differential Effect on Expression of Igf1 and Trp53 in the CNS and Peripheral Tissues of Two Different Mouse Models of Spinal Muscular Atrophy - Donoghue, Morgan (Université d'Ottawa / University of Ottawa, 2023)
Spinal Muscular Atrophy (SMA) is a debilitating neurodegenerative disease resulting in death of the lower motor neurons, muscle atrophy, and in severe cases death. Due to mutations or deletions in the Survival Motor Neuron 1 (SMN1) gene, levels of functional SMN protein product are decreased. While SMA was previously described as a motor neuron exclusive disorder, recent evidence suggests that many tissue and cell types throughout the body are affected. The objective of our study was to outline the effects of varying levels of SMN depletion on two genes of interest, namely Insulin-like growth factor 1 (Igf-1) and Tumor suppressor protein 53 (Trp53) in multiple tissues throughout disease course. The severe Smn2B/- and mild Smn2B/-; SMN2+/- mouse models of SMA were utilized in our studies to determine the levels of mRNA expression and subsequent protein output for these two genes. We employed RT-qPCR, western blot, and ELISA experimental methods. In Smn2B/- mice, Igf-1 mRNA was substantially decreased in symptomatic liver tissue. This was accompanied by widespread decrease in IGF-1 protein in peripheral tissues. Interestingly, this depletion effect on Igf-1 was not observed in the mild mouse model. Our analysis also showed that Trp53 mRNA was dramatically increased within tibialis anterior skeletal muscle of symptomatic Smn2B/- mice, alongside an upregulation of factors involved in p53 mediated apoptosis. Once again, this effect was not observed in the mild Smn2B/-; SMN2+/- mouse model. Overall, we have demonstrated that the extent of SMN depletion, determines whether the expression of Igf-1 and Trp53 is perturbed, suggesting that disease severity is an important factor in what pathways are affected. Finally, we show that alterations in gene expression patterns or subsequent protein levels act in a tissue-specific fashion. More investigation is encouraged to highlight IGF-1’s role as a potential SMN-independent therapeutic for SMA.
Keywords: Spinal Muscular Atrophy; IGF-1; Trp53